Determinants for modal shift of school children from private vehicles to public transport a case study in Metro Manila, Philippines. - Reyes, Yvette Kirsten P. (School of Urban and Regional Planning, University of the Philippines Diliman, 2022)
A usual site in Metro Manila are the school areas congested with vehicles, such as private cars, motorcycles, and tricycles, occurring at peak times during the start and end of a school day. Without a proactive intervention, this will worsen the congestion of streets, makes commuting time longer, limits mobility options, and creates higher incidence of accidents. In the discussion of paradigm shift in achieving sustainable transportation, a balance between the push measures (temporary car bans, road pricing, car limited zones, etc.), pull measures (public transport priorities, cycle networks, pedestrian connections, etc.), and incentives to use the more efficient transport modes should be in place. Most studies advocate that to reduce the reliance on private cars and other personal motorized vehicles, alternative forms of travel should be made attractive. However, these studies have also shown that various individual and socio- economic characteristics, as well as their perception to their surroundings, affect the parents' decision in allowing their children to use other alternative modes of transportation other than their private vehicles. With that, the main objective of the study is to explore the factors and consideration of parents that influence their willingness to shift away from private cars for their children's travel to school. Also, the study analysed if their preferred alternative modes would differ under these scenarios: pre and post pandemic, increase in car use charges and independent commute. A total of 109 parents from various schools in Metro Manila, who use their own private cars for their children's school commuting, have participated in the survey. The leading reasons for choosing private car as their current main transport mode are related to concerns about danger from strangers/crime, safer from accidents and more control on when to depart. More than three quarters of the respondents (82.6%) have expressed willingness to shift to other alternative options. Using a binary logistics regression, the sex of the student, distance of house to school, and quality of public transport vehicles were found to be the significant factors in influencing the willingness of the parents to shift from private car to other transport modes. Findings from this research indicate that the improvement of the quality of public transport vehicles may be the most effective in inducing mobility behaviour towards the public/mass transport, as compared with the other identified possible interventions. When the Covid-19 pandemic happened, more parents became unwilling to use alternative transport modes other than their own car. This significant difference in the willingness to shift between pre-pandemic and post pandemic scenarios puts much emphasis to reduce crowding, better seats, and cleaner vehicles in public transport vehicles. Detailed understanding about the preference and attitude of private car users towards public and active transport is of great significance, as these can help policy makers and urban planners to design and create the conditions that would encourage and motivate car users to shift to more sustainable transportation. Policy formulations need to be designed with consideration of promoting safe and healthy journeys using the public and active transport, especially in the new normal. Furthermore, planning for the school location and children's transportation should be an extensive collaboration between the parents, school officials, urban planners, policy makers, city officials and transport authorities to ensure a multi- sector approach in the provision of a good environment around schools that would encourage the use of public and active transports.